Disrupted properties of functional brain networks in major depressive disorder during emotional face recognition: an EEG study via graph theory analysis - Teng, Chao-Lin; Cong, Lin; Wang, Wei; Cheng, Shan; Wu, Min; Dang, Wei-Tao; Jia, Min; Ma, Jin; Xu, Jin; Hu, Wen-Dong (Frontiers in Human Neuroscience, 2024)
Previous neuroimaging studies have revealed abnormal brain network of patients with major depressive disorder (MDD) in emotional processing. While any cognitive task consists of a series of stages, little is yet known about the topology of functional brain networks in MDD for these stages during emotional faces recognition. To address this problem, electroencephalography (EEG)-based functional brain networks of MDD patients at different stages of facial information processing were investigated in this study. First, EEG signals were collected from 16 patients with MDD and 18 age-, gender-, and education-matched normal subjects when they performed a emotional faces recognition task. Second, the global field power (GFP) method was employed to divided group-averaged eventrelated potentials into different stages. Third, using the phase transfer entropy (PTE) approach, the brain networks of MDD patients and normal individuals were respectively constructed for each stage in negative and positive faces processing. Finally, we compared the topological properties of brain networks of each stage between two groups by graph theory approaches. Results showed that the analyzed three stages of emotional faces processing corresponded to specific neurophysiological phases, namely, visual perception, face recognition, and emotional decision making. It was also demonstrated that depressed patients showed abnormally decreased characteristic path length at the visual perception stage of negative face recognition and normalized characteristic path length in the stage of emotional decision making during positive face processing compared to healthy subjects. Furthermore, while both the MDD and normal groups' brain networks were found to exhibit the small-world network characteristics, the brain network of depression patients tended to be a randomization. Moreover, for patients with MDD, the centro-parietal region may lose its status as a hub in the process of facial expressions identification. Together, our findings suggested that altered emotional function in MDD patients might be associated with disruptions in the topological organization of functional brain networks during emotional faces recognition, which further deepened our understanding of the emotion processing dysfunction underlying MDD.